From Subsistence to Sustainability: Evaluating the Livelihood Outcomes of Agroforestry in Kavrepalanchok, Nepal - Timsina, Tirtha Raj; Rijal, Nirajan (Nepalese Journal of Development and Rural Studies, 2024)
Agroforestry in Nepal is considered as a key driver of sustainable livelihood which links agriculture, economy and environment for income generation and resource conservation. This study examines the evolving agroforestry practices in Bethanchwok Rural Municipality, Kavrepalanchok, Nepal, emphasizing their contribution to sustainable livelihoods. Using a mixed-methods approach, primary data are collected through household surveys, key informant interviews, and field observations, while secondary data are gathered from scholarly sources and government records. Findings indicate a shift from traditional subsistence-based farming to commercial oriented agroforestry remarkably contributing increased farm output and income, food security, and surplus time for women due to easy access to fuelwood, fodder and such. Despite its contributions to food security, income diversification, and environmental conservation, agroforestry faces barriers such as policy gaps, limited market access, labour shortage, and insufficient local governance support. The study concludes that agro forestry is indispensable for sustainable rural development and recommends policy reforms, capacity-building initiatives, and improved market infrastructure.